2021
DOI: 10.1039/d1ra02610k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature fluctuation on colour change and softening of postharvest sweet cherry

Abstract: The inevitable temperature fluctuation induced anthocyanin synthesis, phenolic metabolism, and alkali-soluble pectin degradation, which lead to sweet cherry enzymatic browning and softening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…High temperatures induced fruit softening, commonly accompanied by an increase in cell wall hydrolysis enzyme activity and the modification of the cell wall composition, which were impacted by the release of ethylene and respiration [ 7 , 25 ]. The increase in ambient temperature to 15 °C and 20 °C promoted the production of ethylene and respiration, as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High temperatures induced fruit softening, commonly accompanied by an increase in cell wall hydrolysis enzyme activity and the modification of the cell wall composition, which were impacted by the release of ethylene and respiration [ 7 , 25 ]. The increase in ambient temperature to 15 °C and 20 °C promoted the production of ethylene and respiration, as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Low temperatures could decrease enzyme activity, delaying the softening of peach fruit [ 30 ]. Some researchers reported that a halfway temperature increase or temperature fluctuation during storage could increase the activity of PME and PG, accelerating the degradation of pectin and fruit softening [ 7 , 31 ]. In our previous research [ 18 ], when the ambient temperature rose to 25 °C during the supply chain the peach cell wall pectin content changed significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be one explanation for the increased enzyme activity in the control group during the later stage of storage. POD can combine with polyphenols in fruit to produce brown anthraquinone compounds (Xin et al, 2021). From this perspective, the reduction in POD activity is beneficial to slow down the browning of goji berries, and it happens that the L * value can be used as an indicator of the browning reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The activities of PPO, POD were measured according to the method of Xin et al . (2021). A total of 5 g sample was grinded and homogenised in ice bath, and then 5 mL of extraction buffer (1 mmol PEG, 4% PVPP, and 1% Triton X‐100) was added before being centrifuged at 10 000 g at 4 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%